Resolving the Ophioderma longicauda (Echinodermata: Ophiuroidea) cryptic species complex: five sisters, three of them new - Stöhr, Sabine; Weber, Alexandra Anh-Thu; Boissin, Emilie; Chenuil, Anne (European Journal of Taxonomy, 2020)
The conspicuous Mediterranean brittle star Ophioderma longicauda (Bruzelius, 1805) has been discovered to represent a cryptic species complex, consisting of six nuclear clusters with contrasting reproductive modes (broadcast spawners and brooders). Here, O. longicauda is re-described. It is distinguished by a dark reddish-brown colouration both dorsally and on the ventral disc, and multiple tumid dorsal arm plates. One eastern Mediterranean brooding cluster is described as O. zibrowii sp. nov., characterized by a dark olive-green colour both dorsally and on the ventral disc, and single dorsal arm plates. Another brooder is described from Tunisia as O. hybrida sp. nov., with a highly variable morphology that reflects its origin by hybridization of O. longicauda and a brooder (possibly O. zibrowii sp. nov.), leaving the third brooding cluster as morphologically indistinguishable at this point and possibly conspecific with one of the others. The West-African O. guineense Greef, 1882 is resurrected as a valid species, differing morphologically from O. longicauda by predominantly single dorsal arm plates and light green or creamy white ventral side. Also from West Africa, O. africana sp. nov. is described, characterized by a dark brown colour, dorsally and ventrally, and single dorsal arm plates.